Penerapan Model Pembelajaran Questions Students Have pada Mata Pelajaran Fiqih di Kelas XI MA Ishlahul Muslimin Senteluk Kecamatan Batulayar Lombok Barat - Hudatullah, Hudatullah; Rasyidi, Abdul Haris (Lembaga Yasin AlSys, 2025)
The low level of active student participation in fiqh learning has become a critical issue underlying this study. One promising approach to enhance student engagement is the implementation of the questions students have model, which emphasizes the use of student-generated questions as the foundation of the learning process. This study aims to apply this model in fiqh instruction and to identify the challenges and efforts involved in its implementation. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation. Data analysis followed the stages of data reduction, data presentation, and conclusion drawing, with data validity ensured through source, method, and time triangulation. The findings reveal that teachers' skills in applying the questions students have model remain limited, particularly in executing the instructional steps as planned. Internal challenges include teachers’ limited ability to develop varied questions and effectively implement strategies. Externally, students demonstrated low confidence in asking questions and limited skills in formulating them. Additional obstacles included suboptimal classroom management and insufficient learning media. To address these issues, teachers engaged in professional development through training, provided guidance for both teachers and students in question formulation, and prepared instructional media prior to teaching. This study underscores the importance of strengthening both teacher and student capacities to foster fiqh learning that is active, participatory, and reflective.